Perception of Diet Control and Physical Activity Housewives: Experiences and Barrier - Mahendro Prasetyo Kusumoa (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
There is a change in lifestyle due to the current era of globalization. This study aims to explore the perception of a healthy diet and physical activity in controlling blood glucose among housewives. This research design uses qualitative methods. The study was conducted in Yogyakarta from January to March 2020. The instrument used was an in-depth interview guide. The characteristics of the respondents are 20 housewives aged 26-65 years and residents of Yogyakarta. In-depth interviews guideline. The instrument was used to obtain answers to questions related to physical activity and diet control, including barriers and their actions in controlling blood glucose. The data collection was through in-depth interview techniques with open questions. Participants were determined by purposive sampling with the maximum variation approach. The instrument utilized an interview guide. The research data were analyzed utilizing open code. The analyzing data process through data transcripts, coding, categorization and determining themes. In ensuring the research validity, triangulation was carried out. The majority of respondents didn't do physical activity and control their eating patterns. Most of them assume that walking and cycling at least 10 minutes every day is enough to maintain health, including blood glycose. The conclusion in this study is the majority housewife don't know how to control diet and physical activity proper. This is caused by the lack of knowledge about a healthy lifestyle.